A rare case of paediatric stridor caused by achalasia. Issue 7 (July 2015) - Barr, J G; Dean, H; Morrison, G
Abstract Objective: This paper reports a case of achalasia in a 12-year-old girl who presented with stridor. Case report: An otherwise healthy 12-year-old girl presented to the ENT clinic with an 18-month history of dysphagia and noisy breathing on eating. Flexible fibre-optic examination showed a normal larynx with normal vocal fold movements. Fibre-optic endoscopic evaluation of swallowing was normal initially, but biphasic stridor occurred after several swallows. Microlaryngoscopy, bronchoscopy and upper oesophagoscopy showed a dilated oesophagus with normal mucosa. Bronchoscopy showed tracheomalacia of the distal trachea, which reduced the airway by approximately 75 per cent. This was caused by posterior compression from redundant oesophageal mucosa with dilatation as a result of retained fluids. Videofluoroscopy suggested achalasia, which was confirmed by oesophageal manometry. Her symptoms improved following a Heller's myotomy. Conclusion: This is the first paediatric case in the English literature of achalasia presenting with stridor. The condition was correctable with surgical intervention.